1998
DOI: 10.1007/bf02404084
|View full text |Cite
|
Sign up to set email alerts
|

Bäcklund transformations of (2+1)-dimensional integrable systems

Abstract: (the theory of Egorov curvilinear orthogonal systems of coordinates in R3), and some other cases. They also derived nonlinear superposition formulas for all these cases. In the modern theory of (1 + I)-dimensional nonlinear integrable systems of partial differential equations, the B~icklund transformations (see [16, 17]) and the corresponding nonlinear superposition formulas have been obtained for most such systems.A theory of Bacldund transformations is also .available for (2 + l)-dimensional nonlinear integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this connection, we point out that it was Bianchi who derived a Bäcklund transformation for triply orthogonal systems of surfaces which was based on the Ribaucour transformation. Remarkably, he demonstrated that, for any choice of the parameters u i , the position vector r of the seed orthogonal coordinate system and its Bäcklund transforms r 1 , r 2 , r 12 = r 21 lie on a circle (Bianchi 1923(Bianchi -1927Ganzha & Tsarev 1996). Thus, iterative application of Bianchi's transformation generates cyclic and hence orthogonal lattices (cf.…”
Section: (A) Definition and Propertiesmentioning
confidence: 99%
“…In this connection, we point out that it was Bianchi who derived a Bäcklund transformation for triply orthogonal systems of surfaces which was based on the Ribaucour transformation. Remarkably, he demonstrated that, for any choice of the parameters u i , the position vector r of the seed orthogonal coordinate system and its Bäcklund transforms r 1 , r 2 , r 12 = r 21 lie on a circle (Bianchi 1923(Bianchi -1927Ganzha & Tsarev 1996). Thus, iterative application of Bianchi's transformation generates cyclic and hence orthogonal lattices (cf.…”
Section: (A) Definition and Propertiesmentioning
confidence: 99%
“…Later in [1], see also [2], it was done in three dimensional case and in [9] one can find the extension to any dimension. Recently, in [10] three Ribaucour transformations were iterated in 3-dimensional space to get some results related with permutability. The permutability theorem for the scalar fundamental was established in [11].…”
mentioning
confidence: 99%
“…For example, for j = i, the use of (6), (20) and (15) leads to the desired result. The i-th derivative must be treated with more care, in fact, we have to start with the alternative expressions…”
Section: From Vertex Operators To Fundamental Transformationsmentioning
confidence: 99%
“…For j = i one just take the derivative and then uses ( 9), ( 6), (20) and (15). The j = i case requires the use of the following expression for C (i) ( it derives from (20))…”
Section: From Vertex Operators To Fundamental Transformationsmentioning
confidence: 99%
See 1 more Smart Citation